Spatiotemporal Analysis of Developing Brain Networks - He, Ping; Xu, Xiaohua; Zhang, Han; Li, Gang; Nie, Jingxin; Yap, Pew-Thian; Shen, Dinggang (Frontiers in Neuroinformatics, 2018)
Recent advances in MRI have made it easier to collect data for studying human structural and functional connectivity networks. Computational methods can reveal complex spatiotemporal dynamics of the human developing brain. In this paper, we propose a Developmental Meta-network Decomposition (DMD) method to decompose a series of longitudinal networks into a set of Developmental Meta-networks (DMs), which reveal the underlying changes in connectivity over development. DMD circumvents the limitations of traditional static network decomposition methods by providing a novel exploratory approach to capture the spatiotemporal dynamics of longitudinal networks. We apply this method to longitudinal structural correlation networks of cortical thickness across subjects at 3-20 years of age, and identify four DMs that smoothly evolve over three stages, i.e., 3-6, 7-12, and 13-20 years of age. We analyze and highlight the characteristic connections of each DM in relation to brain development.